Culture-negative periprosthetic joint infections. Issue 10 (7th October 2019) - Palan, Jeya; Nolan, Ciaran; Sarantos, Kostas; Westerman, Richard; King, Richard; Foguet, Pedro
Abstract : Culture-negative periprosthetic joint infections (CN-PJI) pose a significant challenge in terms of diagnosis and management. The reported incidence of CN-PJI is reported to be between 7% and 15%. Fungi and mycobacterium are thought to be responsible for over 85% of such cases with more fastidious bacteria accounting for the rest. With the advent of polymerase chain reaction, mass spectrometry and next generation sequencing, identifying the causative organism(s) may become easier but such techniques are not readily available and are very costly. There are a number of more straightforward and relatively low-cost methods to help surgeons maximize the chances of diagnosing a PJI and identify the organisms responsible. This review article summarizes the main diagnostic tests currently available as well as providing a simple diagnostic clinical algorithm for CN-PJI. Cite this article: EFORT Open Rev 2019;4:585-594. DOI: 10.1302/2058-5241.4.180067